Two interbreeding populations of Saccharomyces cerevisiae strains coexist in cachaça fermentations from Brazil. Issue 2 (6th November 2013) - Badotti, Fernanda; Vilaça, Sibelle T.; Arias, Armando; Rosa, Carlos A.; Barrio, Eladio
Abstract In this study, the phylogenetic relationships between cachaça strains of Saccharomyces cerevisiae isolated from different geographical areas in Brazil were obtained on the basis of sequences of one mitochondrial (COX2) and three nuclear (EGT2, CAT8, and BRE5) genes. This analysis allowed us to demonstrate that different types of strains coexist in cachaça fermentations: wine strains, exhibiting alleles related or identical to those present in European wine strains; native strains, containing alleles similar to those found in strains isolated from traditional fermentations from Latin America, North America, Malaysian, Japan, or West Africa; and their intraspecific hybrids or 'mestizo' strains, heterozygous for both types of alleles. Wine strains and hybrids with high proportions of wine‐type alleles predominate in southern and southeastern Brazil, where cachaça production coexists with winemaking. The high frequency of 'wine‐type' alleles in these regions is probably due to the arrival of wine immigrant strains introduced from Europe in the nearby wineries due to the winemaking practices. However, in north and northeastern states, regions less suited or not suited for vine growing and winemaking, wine‐type alleles are much less frequent because 'mestizo' strains with intermediate or higher proportions of 'native‐type' alleles are predominant.